Infographic. Running myth: strength training should be high repetition low load to improve running performance - Alexander, J. L. N.; Barton, C. J.; Willy, R. W. (British Journal of Sports Medicine, 2020)
It is recommended that runners seek the assistance of an experienced health professional or strength and conditioning coach to ensure they start out safely and get the most out of their strength training program.